PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN DAN PENILAIAN PASAR DENGANCORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Citra Chairunissa; Raden Rosiyana Dewi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
The objective of the emperical study is to examine and to analyze 1) The Influence of Intellectual Capital to Financial Performance, 2 ) The Influence of Intellectual Capital to Market Value, 3) The Influence of Intellectual Capital to Financial Performance with Corporate Governance as an Moderating 4) The Influence of Intellectual Capital to Market Value with Corporate Governance as an Moderating Variable. The sample of this emperical study is the company financing company that listed in the Indonesia Stock Exchange (IDX) 2010-2012. This research uses purposive sampling method. Data analysis techniques include 1) Descriptive statistics, 2) Normality Test, 3) Classical Test Assumptions : Multicollinearity and Heteroskidastity , 4) Regression Testing : Coefficient of Determination Test , F Test , danUji T. The results of this empirical study are 1) Intellectual Capital significant positive effect on the company 's financial performance , 2) Intellectual Capital significant negative effect on market valuation , 3) Intellectual Capital no significant effect on the financial performance of companies with moderated Corporate Governance, 4) Intellectual Capital had no significant effect assessment of the performance market with moderated Corporate Governance